Changes in Bacterial Species and Antibiotic Sensitivity in Intensive Care Unit: Acquired Urinary Tract Infection during 10 Years Interval (2001-2011 ) - Yoon, byung il; Kim, Hyo Sin; Kim, Sung Dae; Cho, Kang Jun; Kim, Sun Wook; Ha, U-Syn; Cho, Yong-Hyun; Sohn, Dong Wan (Urology Journal, 2014)
Abstract Purpose: Patients in the intensive care unit (ICU) are usually at greater risk for acquiring urinary tract infections (UTIs). Few studies have focused on UTIs specifically acquired within the ICU. We studied the change in bacterial species causing UTIs in ICU admitted patients in 2001 and 2011. Materials and Methods: We reviewed the medical records of a total of 2,890 ICU patients who had undergone urine culture in 2001 and 2011 at the Yeouido and Bucheon St. Mary's hospitals. Changes in causative organisms and their antibiotic sensitivity between the years 2001 and 2011 were analyzed. Results: Escherichia coli (E. coli) was the most common organism in ICU-acquired UTIs in 2001 and 2011 in our study. The pathogens that significantly increased in 2011 compared to 2001 were Pseudomonas, and Klebsiella species (P < .05). In 2011gram-negative organisms showed relatively higher sensitivities to amikacin, imipenem, and tazocin (72.0%, 77.5% and 76.1%, respectively), whereas they showed relatively lower sensitivities to third-generation cephalosporins and ciprofloxacin (55.2% and 45.0%, respectively). In 2011gram-positive organisms showed high sensitivities to teicoplanin and vancomycin (91.1% and 87.9%, respectively), whereas they showed low sensitivities to ampicillin and ciprofloxacin (24.1% and 25.5%, respectively). The antibiotic resistance rate of Pseudomonas species was nearly doubles that of E. coli. Conclusion: Infections caused by Pseudomonas and Klebsiella species were found to have increased significantly in 2011. Pseudomonas species had a significantly lower susceptibility to antibiotic sensitivity than other identified organisms.